Clonal dissemination of drug-resistant Acinetobacter baumannii in Thailand: insights from nationwide molecular typing - Avzun, Tasnuva; Nitayanon, Perapon; Yungyuen, Thitiya; Kamolvit, Witchuda; Wongsurawat, Thidathip; Chewapreecha, Claire; Kiratisin, Pattarachai; Thaipisuttikul, Iyarit (The Journal of Infection in Developing Countries, 2025)
Introduction: Drug-resistant Acinetobacter baumannii poses a global health crisis, especially in Asia. It has a propensity to become clonally endemic in healthcare settings. However, its clonal distribution in a broad geographic area is unclear. Methodology: The clonality of A. baumannii was characterized nationwide by collecting 572 drug-resistant A. baumannii from 18 hospitals across Thailand regions between 2017–2018 and genotyping them by random amplified polymorphic DNA (RAPD) polymerase chain reaction (PCR) in association with carbapenemase genes data. Results: The results depicted 12 types of RAPD banding. Strikingly, two types were predominant in all hospitals (79%). Of those, 96% harbored the blaOXA-23 gene. The banding pattern matched the preexisting strain in the institution, suggesting an ongoing nationwide circulation of the resistant clone. Interestingly, a unique banding type was identified in high proportion in two nearby hospitals in the northern region (21%, 53/252). Two isolates with the same banding pattern were also identified in a hospital in Bangkok, suggesting the possibility of transfer between regions. Most of the subset of isolates analyzed belonged to sequence type (ST) 2, the most prominent ST in the Asia-Pacific region. Conclusions: This study demonstrated continuous dissemination of predominating A. baumannii clones across the country, and the emergence of endemic hospital-specific clones, all with high burdens of blaOXA-23; suggesting a strong selection for these resistance determinants. In addition, genotyping with RAPD can be a simple and cost-effective epidemiological tool with efficient discriminatory power for A. baumannii in developing countries.